2016
DOI: 10.1063/1.4964140
|View full text |Cite
|
Sign up to set email alerts
|

Dust ion-acoustic cnoidal waves in a plasma with two temperature superthermal electrons

Abstract: An investigation of dust ion-acoustic (DIA) cnoidal waves in unmagnetized collisionless plasma consisting of two temperature superthermal electrons, inertial warm ions, and negatively charged dust grains is presented. Reductive perturbation technique has been used to derive the modified Korteweg-de Vries (mKdV) equation for the study of nonlinear periodic waves. Further, applying the Sagdeev potential approach, energy balance equation is derived. Using the expression for Sagdeev potential in expanded form, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…This has been predicted theoretically for nonlinear waves in various physical systems [34][35][36][37][38][39]. Theories have also been developed specifically for dusty plasmas [40][41][42][43][44][45][46], under various assumptions, predicting cnoidal solutions for nonlinear waves. For example, Yadav et al [40,41] derived a theory predicting a cnoidal solution for dust acoustic waves under an assumption that included Boltzmann electrons and ions and cold dust with fluctuating charges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been predicted theoretically for nonlinear waves in various physical systems [34][35][36][37][38][39]. Theories have also been developed specifically for dusty plasmas [40][41][42][43][44][45][46], under various assumptions, predicting cnoidal solutions for nonlinear waves. For example, Yadav et al [40,41] derived a theory predicting a cnoidal solution for dust acoustic waves under an assumption that included Boltzmann electrons and ions and cold dust with fluctuating charges.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yadav et al [40,41] derived a theory predicting a cnoidal solution for dust acoustic waves under an assumption that included Boltzmann electrons and ions and cold dust with fluctuating charges. Saini et al [45] used a model consisting of two components of superthermal electrons to study cnoidal waves for nonlinear dust ion-acoustic waves while Tolba et al [46] studied cnoidal forms of dust acoustic waves in positively charged dusty plasmas. The basic nonlinear model equation, of which the cnoidal form is an exact solution, is the classical Korteweg de Vries (KdV) equation that has its historical origins in the study of surface water waves.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical results have shown the signature of the fast particles in the space and laboratory DPM. These fast particles are governed by the super‐thermal/ κ ‐distribution that was first introduced by the Vasyliunas .…”
Section: Introductionmentioning
confidence: 89%
“…The κ ‐distribution overlaps with the Maxwellian distribution when the super‐thermal parameter κ in the κ ‐distribution travels to infinite (i.e., κ → ∞). Saini and Sethi examined DIA‐CWs in a four component DPM, and found that the width and amplitude of the DIA‐CWs decrease with increasing value of κ . Alam et al investigated solitary waves (SWs) and DLs regarding DIAWs in a DPM in the presence of super‐thermal electrons, and observed that the amplitude of the negative DLs potential increases with super‐thermal parameter κ .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation